Thermal and optical properties of benzofuran-2-yl 3-phenyl-3-methylcyclobutyl thiosemicarbazone - Koca, A; Dagdelen, F; Aydogdu, Y (Elsevier Science Bv, 2004)
The thermal degradation of the benzofaran-2-yl 3-phenyl-3-methylcyclobutyl thiosemicarbazone (CBSC) was studied under air atmosphere using DSC and simultaneous TG/DTA at the temperature range 20-500 degreesC. Thermal melting activation energy which are 308.6 and 307.9 kJ/mol were evaluated using Kissinger method from DSC and DTA curves, respectively. The activation energy of thermal decomposition was calculated using the Ozawa method for two decomposition stages. The experimental results showed that the activation energy of decomposition for non-isothermal behavior are 123.8 and 135.2 kJ/mol for the first (at 5% weight loss) and second (at 20% weight loss) decomposition stages, respectively. By using hot probe method, electrical conduction mechanism of CBSC was found as p-type. The values of thermal activation energy of electrical conduction, E-1 and E-2, as calculated from lnsigma =f(1000/T) curves, were found to be 3.90 and 0.36 eV, respectively. Optical absorption studies in the wavelength range 190-900 nm showed that direct optical band gap of the benzofuran2-yl 3-phenyl-3-methylcyclobutyl thiosemicarbazone is 2.80 eV. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: thermal activation energy; optical band gap; benzofaran; cyclobutane